PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI PADA MATERI TATA SURYA UNTUK SISWA SMP - Isnaini Safira; Wulan Anna Pertiwi (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Online and digital learning is an impact of globalization. Learning activities now come in various forms, such as direct online learning and indirect online learning. Of course, this makes it easier for students to access information. The learning process in schools requires media that suits students' characteristics to achieve learning goals, one of which is increasing learning motivation and a clear understanding of the learning material. When learning Natural Sciences (IPA), especially solar system material, teachers often use conventional media such as printed books, so that students do not get concrete descriptions of celestial bodies or solar system activities, so learning media are needed that can describe solar system material clearly. It is hoped that the solar system animation video will provide a complete explanation of the solar system and other celestial bodies. This research aims to develop animated video-based learning media on solar system material and test its feasibility procedurally, theoretically and practically. The development method used is ADDIE which consists of 5 stages, namely analyze, design, develop, implementation and evaluate. The results of the assessment of the feasibility of solar system animated video-based learning media for junior high school students based on the opinion of media experts obtained a percentage of 96% and were included in the